Female political discourse in the Albanian parliament in democracy and communism - Limaj, Elona (Theoria et Historia Scientiarum, 2024)
This study delves into the transformation of women’s political discourse in Albania amidst significant political and technological shifts in recent decades. Its objective is to systematize the understanding of women’s political discourse within the Albanian parliament, examining its evolution across various historical-political periods and the influence of modern information processes in democratic Albania. Utilizing theoretical methodologies, the research scrutinizes political discourse as a dynamic facet of political communication, with a particular focus on its gender dimensions and its impact on political engagement. The analysis spans several eras: the communist regime, the initial formation of democracy, and the current democratic consolidation phase. It employs a comparative approach to highlight distinct and common features of women’s political discourse across these periods. The study identifies contemporary challenges in female political communication within the Albanian parliament and proposes strategies for their improvement, emphasizing the need to enhance the role of women in Albania’s socio-political sphere. Key lexemes indicative of different historical and political contexts are analyzed to understand the influence of regime shifts on political discourse. The study differentiates between the concepts of political discourse and political communication, offering nuanced insights into these areas. This material reveals the intersection of political, social, and cultural changes in Albania as seen through women’s political discourse. It demonstrates how shifts in political regimes and societal norms have redefined political communication, particularly for women, highlighting their growing involvement and impact in Albania’s political arena. The conclusions provide a comprehensive view of Albania’s evolving socio-political landscape, underlining the increasing significance of women in shaping the nation’s future.